PENGARUH KUALITAS PENETAPAN PAJAK DAN PENAGIHAN PAJAK AKTIF TERHADAP PENCAIRAN TUNGGAKAN PAJAK (Studi Kasus KPP Pratama Semarang Selatan Dan KPP Pratama Semarang Timur) - Umi Dwi Susanti, 11.05.52.0168; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2015)
The study examines the effect of tax determination quality, tax collection with reprimand letter and force letter on Disbursement Tax Arrears. This research was conducted at the KPP Pratama Semarang Selatan and KPP Pratama Semarang Timur. The sampling method used purposive sampling with the observation period 2011 to 2013. Relationship and (or) influence between variableis described by using multiple regression analysis. The result showed that the tax determination quality has positive effect and significant to the Disbursement Tax Arrears. Whereas the tax collection with reprimand letter and force letter had no significant on Disbursement Tax Arrears.Keyword: Tax Determination Quality, Tax Collection, Reprimand Letter, Force Letter, and Disbursement Tax Arrears